PENGGUNAAN “PLANT GROWT PROMOTING RHIZOBAKTERI ” PADA BENIH PADI SAWAH VARIETAS CIGELIS DAN SITUBAGENDIT TERHADAP PERTUMBUHAN DAN HASIL : - - Ni Komang Budiyani; I Wayan Sukasana; I Wayan Lana (Agriculture Faculty of Flores University, 2021)
The Use of “Plant Growth Promoting Rhizobakteri” on Rice Field Seed Cigeulis and Situbagendit Variety on Growth and Outcome. Rice plant is a very important food crop which is the staple food of more than half of the world's population. Rice plants as a rice producers contain nutrients for the human body needs. Rice cultivation affects the availability of nutrients. PGPR is bacteria which has potentiality to forming colonies around the roots to help provide nutrients for plants, facilitate nutrients absorption for plants, and improving the plants’ production. Rhizobakteri is bacteria in rhizosfer which aggressively forming plants’ roots, and give benefits for plants by spur growth. The aimed of this study is to find out the potentiality of PGPR in improving growth and results of rice production. The experimental design that used was randomized block design, with 4 treatments. Growth and the best result that obtained was on treatment (CGIE), which consist of plant height, number of tillers and grain weight. Keywords: Rice, PGPR, Rice Variety and Production Result